Precise Molecular Design of a Pair of New Regioisomerized Fluorophores With Opposite Fluorescent Properties - Wang, Zexin; Li, Renfu; Chen, Li; Zhai, Xin; Liu, Wei; Lin, Xiang; Chen, Liwei; Chen, Nannan; Sun, Shitao; Li, Zhenli; Hao, Jinle; Chen, Xueyuan; et al. (Frontiers in Chemistry, 2022)
Aggregation-induced emission (AIE) has attracted much attention in the past two decades. To develop novel AIE-active materials, ACQ-to-AIE transformation via regioisomerization is one of the most straightforward method. However, most of the reported ACQ-to-AIE transformations are achieved by migrating bulky units. In this work, a facile conversion was realized by migrating a small pyrrolidinyl group from para- to ortho-position on the rofecoxib scaffold. As a result, a pair of new isomers named MOX2 and MOX4 exhibited ACQ behavior and AIE activity, respectively. Moreover, MOX2 also showed solvatochromic, mechanochromic, and acidochromic properties with reversible multi-stimulus behavior. Single crystal X-ray analysis of MOX2 revealed that the molecular conformation and its packing mode were responsible for the AIE emission behavior. Further investigation indicated that MOX2 showed high lipid droplets staining selectivity. Taken together, the current work not only provides a new design philosophy for achieving ACQ-to-AIE conversion by migrating a small pyrrolidinyl group but also presents a promising candidate MOX2 for potential applications such as in security ink, optical recording and biological applications.